2003
DOI: 10.1590/s0004-282x2003000600007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potentially reversible dementias in a dementia outpatient clinic of a tertiary university-affiliated hospital in Brazil

Abstract: -The importance of investigating the etiology for dementia lies in the possibility of treating potentially reversible dementias. The aims of this retrospective study are to determine the prevalence of potentially reversible dementias among 454 outpatients seen at the Cognitive and Behavioral Neurology Unit, Hospital das Clínicas, São Paulo University School of Medicine -Brazil, between the years of 1991 and 2001, and observe their evolution in follow-up. Among the initial 454 patients, 275 fulfilled the DSM-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
4
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
0
27
4
6
Order By: Relevance
“…None of the patients were diagnosed with neurosyphilis. The prevalence in our study is higher than three Brazilian studies 6,21,22 . Takada et al 21 showed a prevalence of potentially reversible dementia was 8% of total sample in a university hospital.…”
Section: Discussioncontrasting
confidence: 79%
“…None of the patients were diagnosed with neurosyphilis. The prevalence in our study is higher than three Brazilian studies 6,21,22 . Takada et al 21 showed a prevalence of potentially reversible dementia was 8% of total sample in a university hospital.…”
Section: Discussioncontrasting
confidence: 79%
“…It is necessary more studies in different regions of our country about early onset dementia, and the ones with senile dementia clearly has showed AD as principal cause of dementia [9][10][11][12][13] . Collaborative researches can clarify this picture.…”
Section: Discussionmentioning
confidence: 99%
“…There are no studies analyzing the prevalence of presenile dementia in our country in a search in MEDLINE. Other authors have reported diagnostic prevalence in senile dementia or overall rates of dementia in their outpatient clinics [9][10][11][12] or institutionalized patients 13 . One report was presented as abstract and has reviewed a considerable number of patients (n= 619) and found a prevalence of 28.6% of presenile dementia 14 .…”
mentioning
confidence: 99%
“…All over the country, few outpatient units mostly from the university [7][8][9][10] , have trained specialists and have given assistance to older persons with dementia and other related disorders, whereas primary and tertiary care are still difficult to find.…”
mentioning
confidence: 99%